The roles of the retinoic acid receptors in growth, differentiation and development. - Costa, Stacy Lara. (University of Ottawa (Canada), 1995)
In the second chapter of this thesis I have looked at the roles of the retinoic acid receptors (RARs) in differentiation by assessing their actions in the retinoic acid (RA) induced differentiation of P19 cells. I used mutant RARs to block the normal differentiation of these cells and then analyzed the possible mechanisms by which these mutants are able to exert such effects. My results indicate that overexpression of a dominant negative RAR (RAR$\alpha$myc) is able to block the RA induced differentiation of P19 cells. I believe that RAR$\alpha$myc acts dominantly by sterically inhibiting the binding of normal transcription complexes to the retinoic acid response element. In the next part of my thesis, I wanted to assess the role of the RARs in tumourigenesis by overexpressing RAR$\alpha$myc in the mammary gland in the mouse. Many cancers arise due to a block in the normal differentiation of an undifferentiated precursor cell and I postulated that the RAR$\alpha$myc, because of its ability to block differentiation, would lead to tumourigenesis in the breast. This transgenic mouse model system has been used to assess the actions of a variety of oncogenes. Expression of my dominant negative RARa did not lead to tumourigenesis in the breast. However due to expression of the mutant RAR in the male reproductive tract these mice were infertile. My data suggests that the infertility arises due to a block in vas deferens caused by excessive production of seminal fluids. In the last part of this thesis I analyzed a novel mechanism by which I believe retinoids are able to integrate their growth signals with other growth signals within the cell. I found that E2F, a transcription factor which induces cell cycle progression, is able to specifically inhibit the actions of the RARs in activating transcription. My data indicates that this is due to E2F squelching of factors from RAR transcription complexes. My analysis suggests that a crucial co-activator which is required for RAR transactivation in P19 cells is being sequestered by E2F leading to the block in RAR transactivation. I believe that utilization of common co-activators by opposing growth signalling pathways is one way in which the cell is able to integrate growth signalling information.
Keywords: Biology, Cell.